The enforcement of laws on blogging in Malaysia and Singapore / Abdul Hadi Omar…[et al.] - Omar, Abdul Hadi; Kamis, Karaarul Azuan; Zulkefly, Fatimahtul Zahrah; Mustafa, Nabilah Huda; Che Alias, Nuradilla (2010)
Due to the rapid changes of technology, there are so many thing had been invented including blog or weblog. People can use this Internet medium to post their views, pictures and even put comments on it. However, blogging also has its advantages where it may contribute to a legal problem such as defamation, sedition, trademark and copyright infringement. The laws are available to govern this problem but it seems like the laws are not being enforced effectively and comprehensively. This study sets out to investigate the effectiveness and comprehensiveness of enforcement of existing laws on blogging such as the Communication Multimedia Act 1998, Defamation Act 1957, Sedition Act 1948 and Copyright Act 1987. This is due to the fact that there are problems in enforcing the existing laws in an effective manner. The existing laws are suitable in governing the legal problem when blogging but there is a need for improvement to cater for cyberspace environment so as to ensure the effective enforcement of the laws in Malaysia.